Organic Carbon Stocks, Dynamics and Restoration in Relation to Soils of Agroecosystems in Ethiopia: A Review - Gebeyehu, Getaneh; Soromessa, Teshome; Teketay, Demel (International Journal of Environment, 2017)
Soils represent the largest carbon pool and play important roles for carbon storage for prolonged periods in agroecosystems. A number of studies were conducted to quantify soil organic carbon (SOC) worldwide. The objective of this review was to evaluate organic carbon stocks, dynamics and restoration in soils of agroecosystems in Ethiopia. Soil data from 32 different observations, representing four different agroecosystems, were analysed. The mean SOC stocks in the four agroecosystems varied and ranged from 25.66 (sub-humid agroecosystem) to 113.17 (humid mid-highland agroecosystems) Mg C ha-1 up to one meter depth. The trend of mean SOC followed (in descending order): humid mid-highland (113.17 Mg C ha-1) > per-humid highland (57.14 Mg C ha-1) > semi-arid (25.77 Mg C ha-1) > sub-humid (25.66 Mg C ha-1). Compared with soils of tropical countries, those in Ethiopian agroecosystems contained low SOC storage potential. This might be associated with differences in measurement and analysis methods as 53.1% of the studies employed the Walkley-Black Method, which is known to underestimate carbon stocks in addition to ecological and management effects. However, shifts of land management from rain-fed to irrigation farming systems exhibited progress in the improvement of mean SOC storage potential. The analyses showed that farming systems involving irrigation sequestered more carbon than rain-fed farm systems. The mean SOC in the various agricultural land uses followed the following trend (in descending order): agroforestry (153.57 Mg C ha-1) > grazing land (34.61 Mg C ha-1) > cereal cultivation (24.18 Mg C ha-1). Therefore, the possible solutions for improvement of organic carbon stocks would be implementation of appropriate restoration strategies based on agroecosystems.INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-6, Issue-1, Dec-Feb 2016/17, page: 1-22